LF refining slag for nickel-based alloy and preparation method of LF refining slag
By using a specific mixing and briquetting process to prepare LF refining slag for nickel-based alloys, the problems of low desulfurization efficiency and insufficient slag physicochemical properties in LF refining of nickel-based alloys are solved. This process achieves high-efficiency desulfurization, rapid slag formation, and low corrosivity, making it suitable for high-efficiency refining of nickel-based alloys.
Patent Information
- Application Number
- CN202510974823.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2026-02-06
AI Technical Summary
Existing technologies for refining nickel-based alloys using LF processes suffer from insufficient desulfurization efficiency, defects in the slag system's physicochemical properties, and compatibility issues with the alloy, leading to excessive sulfur content and frequent production failures.
A specific ratio of alkali powder, acid powder, sodium nitrate, magnesium silicide powder, silicon powder and cryolite is used to prepare LF refining slag for nickel-based alloys. The LF refining slag for nickel-based alloys is formed by briquetting process. Combined with high silica glass and AOD reduction slag, the basicity and melting point of the slag system are adjusted to promote the escape of sulfides.
It achieves high desulfurization efficiency (90-98%), fast slag formation speed, low erosion and good compatibility, avoids nozzle blockage and furnace lining erosion, and is suitable for high-efficiency refining of nickel-based alloys.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of steelmaking auxiliary materials technology, specifically relating to an LF refining slag for nickel-based alloys and its preparation method. Background Technology
[0002] Nickel-based alloys possess excellent high-temperature performance, high corrosion resistance, high fatigue strength, and high toughness, and are widely used in key areas such as engine turbine disks, combustion chambers, nuclear power steam generator tubes, acid-resistant valves, seawater heat exchangers, and orthopedic implants.
[0003] These alloys are extremely sensitive to sulfur content; even trace amounts of sulfur can form sulfide inclusions, leading to hot brittleness, intergranular corrosion, and a sharp drop in fatigue life. In current production processes, LF refining is the final and crucial step in deep desulfurization, but existing technology suffers from systemic flaws: (1) Insufficient desulfurization efficiency, making it difficult to meet sulfur content standards. Traditional LF refining relies on lime-fluorite slag system, and the auxiliary materials themselves contain sulfur, becoming a source of sulfur pollution; high-temperature desulfurization during the AOD reduction period is limited by high-temperature conditions and has weak control over ultra-low sulfur; VOD mainly decarbonizes and has limited contribution to desulfurization; nickel-based alloys have complex compositions, and their interaction with slag leads to a decrease in sulfur activity. The sulfur capacity of traditional slag systems is insufficient, resulting in sulfur content still exceeding the standard after LF treatment.
[0004] (2) Defects in the physicochemical properties of slag system lead to process failures Slow slag melting rate: Conventional slag systems have high melting points (>1300℃) and high viscosity (>0.50Pa·s), with melting rates exceeding 30 seconds at 1350℃. Uneven coverage leads to incomplete desulfurization reaction. Risk of nozzle blockage: High Al2O3 slag systems tend to form aluminum-oxygen tetrahedral crystal structures, causing the slag to transition from a glassy state to a crystalline state. During continuous casting, crystallization and precipitation can easily block the nozzle, interrupting production. Severe furnace lining erosion: The presence of CaF2 and SiO2 in the slag can easily allow the slag to penetrate and erode magnesium and carbon, accelerating furnace lining damage.
[0005] (3) Technological gaps in the field A comprehensive search revealed no patented technology specifically for LF refining slag for nickel-based alloys. Existing improvements focus on desulfurization of ordinary steel (such as CN112795754A which uses a calcium aluminate slag system). However, the high Ni / Cr content of nickel-based alloys significantly alters the thermodynamics of the slag-steel reaction. Directly applying these technologies would lead to problems such as mismatched slag-metal interfacial tension, decreased inclusion adsorption capacity, incompatibility between slag basicity (CaO / SiO2) and alloy composition, and a desulfurization rate of less than 70%.
[0006] In summary, developing LF refining slag, which combines efficient desulfurization, fast melting rate, low corrosivity, and compatibility with nickel-based alloys, is an inevitable choice to break through the bottleneck in high-end alloy production. Summary of the Invention
[0007] The purpose of this invention is to address the shortcomings of existing technologies by providing an LF refining slag for nickel-based alloys and its preparation method.
[0008] Specifically, the method for preparing LF refining slag for nickel-based alloys provided by this invention includes the following steps: (1) By weight percentage, 27-33% alkali powder, 26-32% acid powder, 6-10% sodium nitrate, 3-5% magnesium silicide powder, 1-3% silicon powder, and 20-30% cryolite are mixed evenly to obtain mixed raw materials; (2) The mixed raw materials are briquetting to obtain LF refining slag for nickel-based alloys.
[0009] The above-mentioned method for preparing LF refining slag for nickel-based alloys includes alkali powder comprising fluorite and lime in a weight ratio of (0.8-1.2):(2.3-2.8); and acid powder comprising high silica glass and AOD reduction slag in a weight ratio of (0.8-1.2):(2.5-3.5).
[0010] In the above-mentioned method for preparing LF refining slag for nickel-based alloys, the particle size of the alkali powder is ≤0.088mm, the particle size of the acid powder is ≤0.088mm, the particle size of the sodium nitrate is 0.074-0.088mm, the particle size of the magnesium silicide powder is 0.044-0.088mm, the particle size of the silicon powder is 0.001-0.044mm, and the particle size of the cryolite is 0.044-0.088mm.
[0011] The above-mentioned method for preparing LF refining slag for nickel-based alloys uses high-silica glass raw materials, which are clay and recycled quartz glass in a weight ratio of (8.5-9.0): (1.0-1.5), and are obtained by firing at 1400-1500℃. The raw materials contain 40-45% mullite phase, 55-60% glass phase, 42-45% Al2O3 content, 50-55% SiO2 content, and 1.5-2% K2O+Na2O content.
[0012] In the above-mentioned method for preparing LF refining slag for nickel-based alloys, the clay has an Al2O3 content of 30-45% and a K2O+Na2O content of 1-2%; the recycled quartz glass has a SiO2 content of 90-95% and a K2O+Na2O content of 1-3%.
[0013] The above-mentioned method for preparing LF refining slag for nickel-based alloys involves fluorite with a CaF2 content of 80-85%, a SiO2 content of 0-8%, a S content of 0-0.15%, and a bulk density of 1.8-2.0 g / cm³. 3The moisture content is 0-0.5%; the lime contains 90-96% CaO, 0-5% MgO, 0-2.5% SiO2, 0-0.04% S, and has an activity of 305-420 ml.
[0014] The above-mentioned method for preparing LF refining slag for nickel-based alloys includes a sodium nitrate purity of 99.3-100%, chloride content of 0-0.15%, water content of 0-0.5%, water-insoluble content of 0-0.03%, and a pH value of 6.0-8.0 for a 5% solution; the magnesium silicide powder contains 90-99% Mg₂Si and has a bulk density of 1.93-1.98 g / cm³. 3 .
[0015] In the above-mentioned method for preparing LF refining slag for nickel-based alloys, the silicon powder contains 98.5-100% Si and has a bulk density of 2.31-2.35 g / cm³. 3 The cryolite has the following molecular ratios: 1-2.8%, F 53-55%, Al 13-15%, Na 28-32%, and SO4. 2- The loss on ignition is 0-0.4%, the water content is 0-0.2%, and the loss on ignition is 0-2%.
[0016] In the above-mentioned method for preparing LF refining slag for nickel-based alloys, the mixing is carried out in a V-type mixer for 5-15 min at a speed of 10-25 rpm; the briquetting is carried out in a double-roll briquetting machine at a forming pressure of 10-50 MPa and a particle size of 20-50 mm.
[0017] The present invention also provides an LF refining slag for nickel-based alloys, which is prepared by the above-described preparation method.
[0018] The technical solution of the present invention has the following beneficial effects: (1) The method for preparing LF refining slag for nickel-based alloys of the present invention uses conventional crushing, mixing and pelletizing processes. The process is simple and does not require additional production line design. It can be completed on the existing pelletizing production line of Taiyuan Iron & Steel Group. At the same time, due to the hydration of lime, Ca(OH)2 is generated while reducing moisture, which acts as a binder. No additional binder is needed to form pellets. (2) The LF refining slag for nickel-based alloys of the present invention has a significant desulfurization effect. The combination of acid powder and alkali powder provides a high alkalinity environment of 2.8-3.5, which is conducive to desulfurization. When S in the steel enters the slag, magnesium silicide powder can effectively reduce the activity of S in the slag. Under the action of sodium nitrate, it effectively promotes the conversion of sulfides in the slag into SO2 and releases. (3) The LF refining slag for nickel-based alloys of the present invention has a basicity of 2.5-3.5, a melting point of 1000-1300℃, a viscosity of 0.25-0.50 Pa·s, a melting rate of 20-30s at 1350℃, and a desulfurization efficiency of 90-98%; (4) The nickel-based alloy LF prepared by the present invention has good desaturation effect, fast slag formation speed and good coverage effect; strong slag system stability and good compatibility with nickel-based alloys; simple preparation process and no need for binder; protects furnace lining and has low corrosion to ladle furnace lining; will not block water nozzle during continuous casting; and the use of quartz glass and AOD reducing slag is environmentally friendly. Detailed Implementation
[0019] To fully understand the purpose, features, and effects of this invention, the following detailed embodiments are provided. Except as described below, the process methods of this invention employ conventional methods or apparatus in the art. Unless otherwise specified, the terms and expressions used below have the meanings commonly understood by those skilled in the art.
[0020] When a numerical range is disclosed herein, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to an integer, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included. Unless otherwise specified, "%" in this invention refers to weight percentage.
[0021] The LF refining slag for nickel-based alloys prepared by this invention has a desulfurization efficiency of 90-98%, fast slag formation speed, good coverage effect, strong slag system stability, good compatibility with nickel-based alloys, simple preparation process, no need for binder, protects furnace lining, low corrosion to ladle lining, does not clog water nozzle during continuous casting, and is environmentally friendly due to the use of quartz glass and AOD reducing slag.
[0022] Specifically, the method for preparing LF refining slag for nickel-based alloys provided by this invention includes the following steps: (1) By weight percentage, 27-33% alkali powder, 26-32% acid powder, 6-10% sodium nitrate, 3-5% magnesium silicide powder, 1-3% silicon powder, and 20-30% cryolite are mixed evenly to obtain mixed raw materials; (2) The mixed raw materials are briquetting to obtain LF refining slag for nickel-based alloys.
[0023] In practice, when alkali powder and acid powder are not within the scope of protection of this invention, they will directly affect the basicity, viscosity, surface tension, and slagging effect of LF refining slag for nickel-based alloys, thus failing to achieve the purpose of desulfurization. The ratio of sodium nitrate to magnesium silicide powder and silicon powder is crucial for promoting the escape of sulfides and is also the core for preventing the oxidation of alloying elements in steel. Once the ratio is unbalanced, it will have a negative impact on both desulfurization and steelmaking. Cryolite can promote the above reactions at low temperatures, while increasing slagging efficiency and maintaining slag system stability; too much or too little cryolite will disrupt slag system stability and affect the slagging effect.
[0024] In the LF refining slag for nickel-based alloys of the present invention, alkali powder and acid powder are the main components of the LF refining slag for nickel-based alloys, and play a crucial role in maintaining the stability of the slag system, promoting desulfurization, protecting the refractory lining, and reducing nozzle nodule formation.
[0025] In some preferred embodiments, the alkali powder has a particle size ≤0.088mm and comprises fluorite and lime in a weight ratio of (0.8-1.2):(2.3-2.8) (more preferably 1:2.5).
[0026] The fluorite contains 80-85% CaF2, 0-8% SiO2, 0-0.15% S, and has a bulk density of 1.8-2.0 g / cm³. 3 , moisture 0-0.5%.
[0027] The lime contains 90-96% CaO, 0-5% MgO, 0-2.5% SiO2, 0-0.04% S, and has an activity of 305-420 ml.
[0028] In some preferred embodiments, the acid powder has a particle size ≤0.088mm and comprises high silica glass and AOD reduction residue in a weight ratio of (0.8-1.2):(2.5-3.5) (more preferably 1:3).
[0029] The high-silica glass raw material is clay and recycled quartz glass with a weight ratio of (8.5-9.0):(1.0-1.5), which is obtained by firing at 1400-1500℃. The mullite phase accounts for 40-45%, the glass phase accounts for 55-60%, the Al2O3 content is 42-45%, the SiO2 content is 50-55%, and the K2O+Na2O content is 1.5-2%.
[0030] The clay contains 30-45% Al2O3 and 1-2% K2O+Na2O; the recycled quartz glass contains 90-95% SiO2 and 1-3% K2O+Na2O.
[0031] The AOD reducing slag has an alkalinity of 0.9-1.2 and is a reducing slag for smelting nickel-based alloys.
[0032] The function of the AOD reducing slag used in this invention is as follows: nickel-based alloys need to go through AOD→VOD→LF→CC; using reducing slag makes the LF refining slag more compatible with nickel-based alloys, reduces changes in the composition of nickel-gold alloys, reduces the formation of inclusions, and is also beneficial for desulfurization.
[0033] The high-silica glass used in this invention possesses a highly stable glassy phase. When combined with AOD reduction slag, it effectively reduces the slag viscosity and prevents crystallization of the AOD reduction slag. Furthermore, it increases the Al2O3 content in the slag. The high content of basic oxides helps prevent crystallization and stabilizes the glassy phase, while also reducing compatibility with the furnace lining and minimizing slag erosion of the furnace lining.
[0034] In addition, the presence of a large amount of Na2O in the slag system effectively prevents the formation of aluminum-oxygen tetrahedra and promotes the formation of aluminum-oxygen trihedra, stabilizing the glass phase while effectively preventing clogging of the nozzle.
[0035] In this invention, sodium nitrate decomposes at high temperature to release active oxygen (2NaNO3 → Na2O + 2NO2 + O2↑), which is used to oxidize impurities such as carbon, silicon, and phosphorus in molten steel. It also promotes the conversion of sulfides in the slag into SO2, which then escapes. The Na2O generated after decomposition can adjust the basicity of the slag system.
[0036] In some preferred embodiments, the sodium nitrate has a particle size of 0.074-0.088 mm, a purity of 99.3-100%, a chloride content of 0-0.15%, a moisture content of 0-0.5%, a water-insoluble content of 0-0.03%, and a pH value of 6.0-8.0 for a 5% solution; the magnesium silicide powder has an Mg2Si content of 90-99% and a bulk density of 1.93-1.98 g / cm³. 3 .
[0037] In this invention, magnesium silicide, after being oxidized by sodium nitrate, generates highly active SiO2 and MgO. On the one hand, this promotes the melting of refining slag, prevents the crystallization of the glass phase, and is beneficial to the stability of the glass phase; on the other hand, it helps to protect the furnace lining and reduce furnace lining damage.
[0038] In some preferred embodiments, the magnesium silicide powder has a particle size of 0.044-0.088 mm, an Mg2Si content of 90-99%, and a bulk density of 1.93-1.98 g / cm³. 3 .
[0039] In this invention, cryolite lowers the melting point of the slag system, improves its fluidity, and promotes the efficiency of the slag-steel reaction. Through the transfer of fluorine and aluminum via AlF6³⁻ complex ions, it assists in desulfurization and deoxidation, increases slag fluidity to cover the melt surface, and reduces the oxidation loss of alloying elements. Simultaneously, it can provide a large amount of Al₂O₃ combined with Na₂O to stabilize the glassy phase composition, further increasing the slag's fluidity.
[0040] In addition, cryolite and sodium nitrate also have the following synergistic effects: (1) Low-temperature reaction initiation: Cryolite lowers the melting point of the slag system, allowing sodium nitrate to decompose and take effect at a lower temperature; (2) Composite desulfurization: Na2O (from NaNO3) and AlF6 3- (From cryolite) jointly promote the transfer of sulfur into the slag (such as generating Na2S or CaS); (3) Oxidation-protection balance: The oxidizing property of sodium nitrate needs to be controlled by metallic silicon powder and magnesium silicide powder to avoid the burning of alloying elements. The covering effect of cryolite can promote the flow of slag and further avoid this problem.
[0041] In some preferred embodiments, the cryolite has a particle size of 0.044-0.088 mm, a molecular weight ratio of 1-2.8%, F of 53-55%, Al of 13-15%, Na of 28-32%, and SO4 content of 1-2.8%. 2- The loss on ignition is 0-0.4%, the water content is 0-0.2%, and the loss on ignition is 0-2%.
[0042] In this invention, the role of metallic silicon powder is similar to that of magnesium silicide powder: to promote the melting of refining slag, reduce crystallization, and maintain the stability of the glass phase. It also provides SiO2 to maintain stable basicity.
[0043] In some preferred embodiments, the silicon powder has a particle size of 0.001-0.044 mm, a Si content of 98.5-100%, and a bulk density of 2.31-2.35 g / cm³. 3 .
[0044] In some preferred embodiments, the mixing is carried out in a V-type mixer for 5-15 minutes at a speed of 10-25 rpm; the briquetting is carried out in a double-roll briquetting machine at a forming pressure of 10-50 MPa and a particle size of 20-50 mm.
[0045] Optionally, the V-type mixer is model VH-1000, with an effective volume of 800-1200L, a loading coefficient of 30-50%, and is made of 316 stainless steel. The double-roller briquetting machine is model QY-650, with a roller diameter of 600-700mm and a roller surface width of 200-400mm.
[0046] In some preferred embodiments, the method for preparing LF refining slag for nickel-based alloys provided by the present invention further includes a storage step of the prepared LF refining slag for nickel-based alloys.
[0047] Specifically, this involves storing the LF refining slag for nickel-based alloys in a dry, well-ventilated warehouse, avoiding high-temperature and humid environments. To ensure the freshness of the LF refining slag, the time from production to use should be less than 3 days.
[0048] According to the test results, the LF refining slag for nickel-based alloys prepared according to the method of the present invention has a basicity of 2.5-3.5, a melting point of 1000-1300℃, a viscosity of 0.25-0.50 Pa·s, a melting rate of 20-30s at 1350℃, and a desulfurization efficiency of 90-98%.
[0049] Example The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments, unless otherwise specified, were performed according to conventional methods and conditions. The raw materials used in the following embodiments were all commercially available.
[0050] The parameters of the equipment and materials involved in each embodiment are described as follows: The raw materials for high-silica glass are clay and recycled quartz glass in a ratio of 9.0:1.3, and the firing temperature is 1450℃. The mullite phase accounts for 40-45%, the glass phase accounts for 55-60%, the Al2O3 content is 42-45%, the SiO2 content is 50-55%, and the K2O+Na2O content is 1.5-2%.
[0051] The clay contains 30-45% Al2O3 and 1-2% K2O+Na2O.
[0052] The reused quartz glass has a SiO2 content of 90-95% and a K2O+Na2O content of 1-3%.
[0053] The basicity of AOD reducing slag is 0.9-1.2, and it is a reducing slag for smelting nickel-based alloys.
[0054] Cryolite has a particle size of 0.044-0.088 mm, a molecular weight ratio of 1-2.8%, F of 53-55%, Al of 13-15%, Na of 28-32%, and SO4 content of 1-2.8%. 2- The loss on ignition is 0-0.4%, the water content is 0-0.2%, and the loss on ignition is 0-2%.
[0055] Fluorite contains 80-85% CaF2, 0-8% SiO2, and 0-0.15% S, with a bulk density of 1.8-2.0 g / cm³. 3 , moisture 0-0.5%.
[0056] The lime contains 90-96% CaO, 0-5% MgO, 0-2.5% SiO2, 0-0.04% S, and has an activity of 305-420 ml.
[0057] Magnesium silicide powder has an Mg2Si content of 90-99% and a bulk density of 1.93-1.98 g / cm³. 3 .
[0058] The silicon content of the metallic silicon powder is 98.5-100%, and the bulk density is 2.31-2.35 g / cm³. 3 .
[0059] The sodium nitrate has a purity of 99.3-100%, and the chloride (Cl) content is... - The concentrations of the active ingredients are 0-0.15%, the water content is 0-0.5%, the water-insoluble matter is 0-0.03%, and the pH value (for a 5% solution) is 6.0-8.0.
[0060] The V-type mixer model is VH-1000, with an effective volume of 1000L, a loading coefficient of 30-50%, and is made of 316 stainless steel.
[0061] The model of the double-roller briquetting machine is QY-650, with a roller diameter of 650mm and a roller surface width of 300mm.
[0062] Example 1 An LF refining slag for nickel-based alloys and its preparation method. The steps of the preparation method described in this embodiment are as follows: 1. Raw material selection and preparation Raw material selection: high silica glass (5-30mm), AOD reduction slag (0.074-2mm), cryolite (0.044-0.088mm), fluorite (15-40mm), lime (15-40mm), magnesium silicide powder (0.044-0.088mm), metallic silicon powder (0.001-0.044mm), sodium nitrate (0.074-0.088mm).
[0063] Raw material processing: High silica glass and AOD reduction slag are crushed together in a 1:3 ratio to a particle size of less than 0.088 mm to obtain acid powder; fluorite and lime are crushed together in a 1:2.5 ratio to a particle size of less than 0.088 mm to obtain alkali powder.
[0064] 2. Raw material mixing The formula consists of: 27% alkali powder, 32% acid powder, 6% sodium nitrate, 3% magnesium silicide powder, 2% silicon powder, and 30% cryolite.
[0065] Mix evenly: Use a V-type mixer to mix the above powder for 10 minutes at a speed of 15 rpm.
[0066] 3. Ball pressing treatment The above-mentioned powder, which is mixed evenly, is briquetteed using a double-roller briquetting machine at a forming pressure of 25 MPa and a particle size of 30 mm.
[0067] 4. Storage Storage conditions: Store in a dry, well-ventilated warehouse, avoiding high temperature and humid environments.
[0068] Storage time: To ensure the freshness of LF refining residue, the time from production to use is 3.0 days.
[0069] The LF refining slag for nickel-based alloys prepared in this embodiment has the following properties: basicity 2.8, melting point 1251℃, viscosity 0.42 Pa·s, melting rate at 1350℃ 29s, and desulfurization efficiency 90%.
[0070] Example 2 An LF refining slag for nickel-based alloys and its preparation method. The steps of the preparation method described in this embodiment are as follows: 1. Raw material selection and preparation Raw material selection: high silica glass (5-30mm), AOD reduction slag (0.074-2mm), cryolite (0.044-0.088mm), fluorite (15-40mm), lime (15-40mm), magnesium silicide powder (0.044-0.088mm), metallic silicon powder (0.001-0.044mm), sodium nitrate (0.074-0.088mm).
[0071] Raw material processing: High silica glass and AOD reduction slag are crushed together in a 1:3 ratio to a particle size of less than 0.088 mm to obtain acid powder; fluorite and lime are crushed together in a 1:2.5 ratio to a particle size of less than 0.088 mm to obtain alkali powder.
[0072] 2. Raw material mixing The formula is prepared in the following proportions: 30% alkali powder, 32% acid powder, 10% sodium nitrate, 5% magnesium silicide powder, 3% silicon powder, and 20% cryolite.
[0073] Mix evenly: Use a V-type mixer to mix the above powder for 5 minutes at a speed of 17 rpm.
[0074] 3. Ball pressing treatment The above-mentioned powder, which is mixed evenly, is briquetteed using a double-roller briquetting machine at a forming pressure of 25 MPa and a particle size of 30 mm.
[0075] 4. Storage Storage conditions: Store in a dry, well-ventilated warehouse, avoiding high temperature and humid environments.
[0076] Storage time: To ensure the freshness of LF refining residue, the time from production to use is 2.0 days.
[0077] The LF refining slag for nickel-based alloys prepared in this embodiment has the following properties: basicity 3.0, melting point 1113℃, viscosity 0.32 Pa·s, melting rate at 1350℃ 24s, and desulfurization efficiency 93%.
[0078] Example 3 An LF refining slag for nickel-based alloys and its preparation method. The steps of the preparation method described in this embodiment are as follows: 1. Raw material selection and preparation Raw material selection: high silica glass (5-30mm), AOD reduction slag (0.074-2mm), cryolite (0.044-0.088mm), fluorite (15-40mm), lime (15-40mm), magnesium silicide powder (0.044-0.088mm), metallic silicon powder (0.001-0.044mm), sodium nitrate (0.074-0.088mm).
[0079] Raw material processing: High silica glass and AOD reduction slag are crushed together in a 1:3 ratio to a particle size of less than 0.088 mm to obtain acid powder; fluorite and lime are crushed together in a 1:2.5 ratio to a particle size of less than 0.088 mm to obtain alkali powder.
[0080] 2. Raw material mixing The formula is as follows: 27% alkali powder, 28% acid powder, 10% sodium nitrate, 5% magnesium silicide powder, 3% silicon powder, and 27% cryolite.
[0081] Mix evenly: Use a V-type mixer to mix the above powder for 13 minutes at a speed of 20 rpm.
[0082] 3. Ball pressing treatment The above-mentioned powder, which is mixed evenly, is briquetteed using a double-roller briquetting machine at a forming pressure of 25 MPa and a particle size of 30 mm.
[0083] 4. Storage Storage conditions: Store in a dry, well-ventilated warehouse, avoiding high temperature and humid environments.
[0084] Storage time: To ensure the freshness of LF refining residue, the time from production to use is 1.5 days.
[0085] The LF refining slag for nickel-based alloys prepared in this embodiment has the following properties: basicity 3.2, melting point 1056℃, viscosity 0.27 Pa·s, melting rate at 1350℃ 21s, and desulfurization efficiency 95%.
[0086] Example 4 An LF refining slag for nickel-based alloys and its preparation method. The steps of the preparation method described in this embodiment are as follows: 1. Raw material selection and preparation Raw material selection: high silica glass (5-30mm), AOD reduction slag (0.074-2mm), cryolite (0.044-0.088mm), fluorite (15-40mm), lime (15-40mm), magnesium silicide powder (0.044-0.088mm), metallic silicon powder (0.001-0.044mm), sodium nitrate (0.074-0.088mm).
[0087] Raw material processing: High silica glass and AOD reduction slag are crushed together in a 1:3 ratio to a particle size of less than 0.088 mm to obtain acid powder; fluorite and lime are crushed together in a 1:2.5 ratio to a particle size of less than 0.088 mm to obtain alkali powder.
[0088] 2. Raw material mixing The formula consists of 33% alkali powder, 26% acid powder, 7% sodium nitrate, 4% magnesium silicide powder, 1% silicon powder, and 29% cryolite.
[0089] Mix evenly: Use a V-type mixer to mix the above powder for 15 minutes at a speed of 25 rpm.
[0090] 3. Ball pressing treatment The above-mentioned powder, which is mixed evenly, is briquetteed using a double-roller briquetting machine at a forming pressure of 25 MPa and a particle size of 30 mm.
[0091] 4. Storage Storage conditions: Store in a dry, well-ventilated warehouse, avoiding high temperature and humid environments.
[0092] Storage time: To ensure the freshness of LF refining residue, the time from production to use is 1.0 day.
[0093] The LF refining slag for nickel-based alloys prepared in this embodiment has the following properties: basicity 3.4, melting point 1158℃, viscosity 0.36 Pa·s, melting rate at 1350℃ 26s, and desulfurization efficiency 98%.
[0094] The present invention has been disclosed above with reference to preferred embodiments. However, those skilled in the art should understand that these embodiments are merely illustrative of the invention and should not be construed as limiting its scope. It should be noted that any variations and substitutions equivalent to these embodiments should be considered to be covered within the scope of the claims. Therefore, the scope of protection of the present invention should be determined by the scope defined in the claims.
Claims
1. A method for preparing LF refining slag for nickel-based alloys, characterized in that, Includes the following steps: (1) By weight percentage, 27-33% alkali powder, 26-32% acid powder, 6-10% sodium nitrate, 3-5% magnesium silicide powder, 1-3% silicon powder, and 20-30% cryolite are mixed evenly to obtain a mixed raw material; (2) The mixed raw materials are briquetting to obtain LF refining slag for nickel-based alloys.
2. The preparation method according to claim 1, characterized in that, The alkali powder comprises fluorite and lime in a weight ratio of (0.8-1.2):(2.3-2.8); the acid powder comprises high silica glass and AOD reduction slag in a weight ratio of (0.8-1.2):(2.5-3.5).
3. The preparation method according to claim 1, characterized in that, The particle size of the alkali powder is ≤0.088mm, the particle size of the acid powder is ≤0.088mm, the particle size of the sodium nitrate is 0.074-0.088mm, the particle size of the magnesium silicide powder is 0.044-0.088mm, the particle size of the silicon powder is 0.001-0.044mm, and the particle size of the cryolite is 0.044-0.088mm.
4. The preparation method according to claim 2, characterized in that, The high-silica glass raw material is clay and recycled quartz glass with a weight ratio of (8.5-9.0):(1.0-1.5), which is obtained by firing at 1400-1500℃. The raw material contains 40-45% mullite phase, 55-60% glass phase, 42-45% Al2O3 content, 50-55% SiO2 content, and 1.5-2% K2O+Na2O content.
5. The preparation method according to claim 4, characterized in that, The clay has an Al2O3 content of 30-45% and a K2O+Na2O content of 1-2%; the recycled quartz glass has a SiO2 content of 90-95% and a K2O+Na2O content of 1-3%.
6. The preparation method according to claim 2, characterized in that, The fluorite contains 80-85% CaF2, 0-8% SiO2, 0-0.15% S, and has a bulk density of 1.8-2.0 g / cm³. 3 The moisture content is 0-0.5%; the lime contains 90-96% CaO, 0-5% MgO, 0-2.5% SiO2, 0-0.04% S, and has an activity of 305-420 ml.
7. The preparation method according to claim 1, characterized in that, The sodium nitrate has a purity of 99.3-100%, chloride content of 0-0.15%, water content of 0-0.5%, water-insoluble content of 0-0.03%, and a pH of 6.0-8.0 for a 5% solution; the magnesium silicide powder has a Mg₂Si content of 90-99% and a bulk density of 1.93-1.98 g / cm³. 3 .
8. The preparation method according to claim 1, characterized in that, The silicon powder has a Si content of 98.5-100% and a bulk density of 2.31-2.35 g / cm³. 3 The cryolite has the following molecular ratios: 1-2.8%, F 53-55%, Al 13-15%, Na 28-32%, and SO4. 2- The loss on ignition is 0-0.4%, the moisture content is 0-0.2%, and the loss on ignition is 0-2%.
9. The preparation method according to claim 1, characterized in that, The mixing is carried out in a V-type mixer for 5-15 minutes at a speed of 10-25 rpm; the briquetting is carried out in a double-roller briquetting machine at a forming pressure of 10-50 MPa and a particle size of 20-50 mm.
10. An LF refining slag for nickel-based alloys, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.
Citation Information
Patent Citations
Heat treatment process for rapidly obtaining spherical pearlite for medium carbon steel warm forging
CN112795754A